Clifford Geertz's Examination of the Symbolic Significance of Dowry within Islamic Legal Practices - Luthfilhakim, Muhammad; Hidayati, ST Nor Hidayati (Indonesian Association of Islamic Family Law Lecturers, 2023)
Problem statement: The transformation of dowry from an Islamic legal obligation into a symbol of social prestige presents both normative and social challenges; however, it remains understudied within the anthropological perspective of Islamic legal discourse. Objective: This study explores the dynamics of the interpretation of dowry within the marriage practices of the Banyukuning Village community in Semarang Regency, with a particular emphasis on the tension between cultural symbolism and legal obligations as dictated by Islamic law. The central inquiry of this research is how the community interprets and practises dowry within both social and religious contexts. Methods: This study positions itself as an empirical investigation of Islamic law, employing a qualitative interpretative approach. Grounded in Clifford Geertz's theory of cultural symbols and the Maqasid Sharia framework, field data were thematically analysed through interviews, observations, and documentation. Results: The findings indicate that dowries are interpreted in diverse ways: as symbols of social prestige, manifestations of commitment, or mere administrative formalities, contingent upon social background and generational factors. This symbolic practice frequently conflicts with the principles of Sharia law, which advocate simplicity and justice, thus generating social pressure and the potential for domestic conflict. Conclusion: The study concludes that an educational and regulatory approach is necessary to reconcile cultural values with Islamic legal principles, ensuring that the practice of mahar remains relevant and does not become a social burden that undermines the intended purpose of marriage.